Identification of Application Areas of the Steganalytic Approach Based on the Analysis of Spatial Domain of Digital Contents - Akhmamet’eva A.V. (Problems of the Regional Energetics, 2016)
In this paper the identification of application areas of previously developed steganalytic approach based on accounting of quantity of consecutive triads in the matrix of unique colors of digital images, from the point of view of formats of digital contents is carried out. The influence of the size of the digital contents, which are used as containers for the embedding of additional information, on the detection efficiency during steganalysis is analyzed. As a result of fulfilled computational experiments, it has beet stated that the developed approach is effective for digital content in losses formats, and it has been turned out a restriction on size of the containers. Results of computational experiments are demonstrated.